ANALYSIS OF RISK COVERAGE AGREEMENT BETWEEN PT. J&T AND AN INSURANCE COMPANY FOR DELIVERY OF CONSUMER GOODS IN THE CONTEXT OF KAFALAH CONTRACT - Jarmanisa; Siti Mawar; Chairul Fahmi; Azka Amalia Jihad (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
The risk coverage agreement by PT JNT has been regulated in the Standard Operating Procedure which already has provisions and liability for the loss of consumer goods delivery. The responsibility of compensation can be given by means of guarantees submitted to users of transport services in the form of material and immaterial guarantees. Risk coverage provided by PT JNT to consumers can be in the form of compensation with different counts, seen from the insured goods. Compensated goods can be in the form of delay, damage, or loss. Based on these facts, the problems in this thesis are: How is the risk coverage agreement made by PT JNT with an insurance company to protect consumer shipping goods? How is the fulfilment of the agreed agreement clause in the claim process carried out by PT. JNT? and how is the perspective of the kafalah contract on the risk coverage agreement at PT. JNT with insurance companies in consumer shipments. In this research, the author uses an empirical juridical research approach and qualitative research type. Data collection in this case was obtained by interview and documentation techniques. The results of this study indicate that the consumer protection system implemented by PT JNT is not as effective as the one implemented by the insurance company sometimes not in accordance with the agreement and the Consumer Protection Law contained in Law Number 8 Year 1999. Risk coverage for the safety of goods is in accordance with the review of the concept of kafalah in fiqh muamalah where coverage for the safety of goods rests on the concept of helping.